(untitled) (Linguist, 2025)
The research addresses one of the issues of textual linguistics and discourse analysis, namely the construction of the text and its creativity, and the trajectories it leads, after much research in the analysis of discourse and taking into account its components, and the issue of accompanying the text in the construction process has not received enough research. Among the terms and concepts that are part of the conceptual apparatus are: the formation of the text, the construction of the text, the creation of the text, the terms having the same meaning or the same meanings of convergence, because they have a single purpose, which is the composition of the text after the lessons learned from analysis analysis and dismantling. The composition and composition of the text are many images and manifestations that vary according to the author’s goals, including literary creativity and the need for annexation and regulation of a new text in a form that corresponds to the image of the mind that I wish to convey to the recipient and involve him in perception and involvement. The construction of the text is an intentional act aimed at uniting the elements of the building and joining at certain scales. If this textual structure is creative, it can be conceived only in the context of the interaction between the same author and his reality and his linguistic balance, which has its angle and tames it in different ways that are appropriate to the methods of construction. , systems and composition, including what is common to the writer and writers. And precipitated in itself, which is a fingerprint of his fingerprints and his taste that sets him apart from other Paradigm. It is his method of combining linguistic forms, symbolic elements and a scattered vocabulary, as well as the selection of words, tools and letters.